Disease-specific structural changes in thalamus and dentatorubrothalamic tract in progressive supranuclear palsy - Surova, Yulia (Neuroradiology, 2015)
INTRODUCTION: The aim of this study is to identify disease-specific changes of the thalamus, basal ganglia, pons, and midbrain in patients with progressive supranuclear palsy (PSP), Parkinson’s disease (PD), and multiple system atrophy with predominant parkinsonism (MSA-P) using diffusion tensor imaging and volumetric analysis. METHODS: MRI diffusion and volumetric data were acquired in a derivation of 30 controls and 8 patients with PSP and a validation cohort comprised of controls (n = 21) and patients with PSP (n = 27), PD (n = 10), and MSA-P (n = 11). Analysis was performed using regions of interest (ROI), tract-based spatial statistic (TBSS), and tractography and results compared between diagnostic groups. RESULTS: In the derivation cohort, we observed increased mean diffusivity (MD) in the thalamus, superior cerebellar peduncle, and the midbrain in PSP compared to controls. Furthermore, volumetric analysis showed reduced thalamic volumes in PSP. In the validation cohort, the observations of increased MD were replicated by ROI-based analysis and in the thalamus by TBSS-based analysis. Such differences were not found for patients with PD in any of the cohorts. Tractography of the dentatorubrothalamic tract (DRTT) showed increased MD in PSP patients from both cohorts compared to controls and in the validation cohort in PSP compared to PD and MSA patients. Increased MD in the thalamus and along the DRTT correlated with disease stage and motor function in PSP. CONCLUSION: Patients with PSP, but not PD or MSA-P, exhibit signs of structural abnormalities in the thalamus and in the DRTT. These changes are associated with disease stage and impaired motor function.